The transition to an activity-based workplace: Experiences of managers and employees from a sense of coherence perspective in public sector workplaces - Josefine Hansson; Stig Vinberg; Erika Wall; Pär Löfstrand (PLoS ONE, 2025)
Background The Activity-Based Workplace (ABW) is an increasingly popular office design that aims to facilitate new ways of working. Research focusing on the effects of ABWs on various outcomes is growing but there is a lack of studies looking at how managers and employees perceive the transition to ABWs from a salutogenic health-promotion perspective. This study aims to explore how managers and employees experienced a transition period to ABWs through the lens of a sense of coherence. Methods A qualitative design was applied through semi-structured interviews with six managers and focus group interviews with nine employees working in the public sector in Sweden. A content analysis of the interviews was conducted using Aaron Antonovsky’s sense of coherence concept, with the three main aspects of comprehensibility, meaningfulness and manageability acting as a theoretical framework for the analysis. Results Six sub-categories within the three main SOC categories were identified in the material and considered important to the participants during their transition to the ABW. The sub-categories were divided into facilitating factors and barriers to obtaining a sense of coherence. The identified factors were: information and preparation, clear rules, adaptability, leadership, social relations and health and well-being. Conclusions The analysis showed that the managers and employees were exposed to factors which may have acted as both facilitators and barriers to a sense of coherence during the transition to the ABW. When implementing ABWs, consideration must be given to the facilitators and barriers identified in this study during the transition process. The sense of coherence framework appears valuable for gaining a deeper knowledge of managers’ and employees’ experiences during the transition to ABW.